Efektivitas Penegakan Qanun Nomor 6 Tahun 2018 dalam Penanganan Gelandangan dan Pengemis di Kota Banda Aceh: Pendekatan Hukum dan Masyarakat - Rezeki Rezeki; Muhammad Nur; Siti Rahmah (STAI Syekh Abdur Rauf, Aceh Singkil, 2026)
The phenomenon of homelessness and begging in Banda Aceh reflects a complex socio-legal issue within the framework of Islamic local law (qanun). This study aims to analyze the effectiveness of the enforcement of Qanun No. 6 of 2018 on Public Order and Social Tranquility from a law and society perspective. The research employs an empirical legal method using juridical, sociological, and conceptual approaches. Data were collected through document analysis, field observations, and interviews with 12 informants, including municipal police officers (Satpol PP), social service officials, and homeless individuals and beggars. Informants were selected through purposive sampling based on their direct involvement in law enforcement and social realities. The findings reveal three main points. First, the persistence of homelessness and begging is shaped by structural and cultural factors, including poverty, unemployment, unskilled urbanization, and societal compassion practices. Second, law enforcement mechanisms—such as patrols, raids, data collection, and rehabilitation—remain ineffective due to the inconsistent application of sanctions prescribed by the qanun. Third, institutional and socio-cultural constraints, including limited resources, weak inter-agency coordination, inadequate rehabilitation facilities, and public behavior, hinder effective implementation. This study argues that the effectiveness of Islamic local law enforcement depends not only on normative regulations but also on institutional capacity, governance consistency, and socio-cultural integration. Strengthening these aspects is essential to ensure that qanun functions as an effective instrument of social order and justice. [Fenomena gelandangan dan pengemis di Kota Banda Aceh merupakan persoalan sosial yang kompleks dalam kerangka hukum lokal berbasis syariat (qanun). Penelitian ini bertujuan untuk menganalisis efektivitas penegakan Qanun Nomor 6 Tahun 2018 tentang Ketertiban dan Ketenteraman Masyarakat dengan pendekatan hukum dan masyarakat (law and society). Penelitian ini menggunakan metode hukum empiris dengan pendekatan yuridis, sosiologis, dan konseptual. Data diperoleh melalui studi dokumen, observasi lapangan, serta wawancara terhadap 12 informan yang terdiri dari Satpol PP, Dinas Sosial, serta gelandangan dan pengemis, yang dipilih melalui teknik purposive sampling. Hasil penelitian menunjukkan tiga temuan utama. Pertama, keberadaan gepeng dipengaruhi oleh faktor struktural dan kultural, seperti kemiskinan, pengangguran, urbanisasi tanpa keterampilan, serta budaya belas kasihan masyarakat. Kedua, penegakan hukum melalui patroli, razia, pendataan, dan rehabilitasi belum efektif karena sanksi dalam qanun tidak diterapkan secara konsisten. Ketiga, implementasi qanun menghadapi kendala kelembagaan dan sosial, meliputi keterbatasan sumber daya, lemahnya koordinasi, minimnya fasilitas rehabilitasi, serta rendahnya partisipasi masyarakat. Penelitian ini menegaskan bahwa efektivitas penegakan hukum berbasis syariat tidak hanya bergantung pada norma hukum, tetapi juga pada kapasitas kelembagaan, konsistensi penegakan, serta integrasi dengan kondisi sosial masyarakat.]